Method for deeply purifying, repairing and regenerating graphite waste residues of waste lithium ion batteries

By ball milling and heating treatment of graphite waste slag and ammonium persulfate, combined with asphalt cross-linking coating and high-temperature carbonization, the problems of metallurgy residue and structural damage in the graphite waste slag of waste lithium-ion batteries are solved, and efficient regeneration of graphite negative electrode materials is achieved. Improved electrochemical performance and production efficiency.

CN119315160AInactive Publication Date: 2025-01-14SHENZHEN GUANGFENG NEW ENERGY TECH INNOVATION CENT CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411733709.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recycle and regenerate graphite negative electrode materials in waste lithium-ion batteries, resulting in poor metallurgical residues, poor particle uniformity, damaged structure and poor electrochemical performance in the graphite waste residue.

Method used

By mixing the graphite waste residue with ammonium persulfate powder, ball milling and pre-oxidation treatment, then heating and stirring in deionized water, deep purified graphite oxide was obtained, followed by asphalt cross-linking coating and high-temperature carbonization treatment to form a regenerated graphite negative electrode. Material.

Benefits of technology

It realizes deep purification and repair of graphite waste slag, improves the electrochemical performance of recycled graphite, makes it suitable for battery-level applications, simplifies operations, improves production efficiency, and reduces the risk of environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315160A_ABST
    Figure CN119315160A_ABST
Patent Text Reader

Abstract

The invention relates to a waste lithium ion battery graphite waste residue deep purification and repair regeneration method, which comprises the following steps: S1, uniformly mixing graphite waste residue with ammonium persulfate powder to obtain mixed powder; s2, the mixed powder is subjected to ball milling and pre-oxidation treatment, and pre-oxidized graphite waste residues obtained after ball milling treatment are obtained; s3, the pre-oxidized graphite waste residues obtained after ball milling treatment are put into deionized water to be heated and stirred, filtering and drying are conducted after heating is completed, and deeply-purified graphite oxide is obtained; s4, performing asphalt crosslinking coating treatment on the deeply purified graphite oxide; s5, a product obtained after coating treatment is subjected to high-temperature carbonization and sieving, the regenerated graphite negative electrode material is obtained, and the obtained regenerated graphite negative electrode material has excellent electrochemical performance. By means of the method, deep purification is conducted on the graphite waste residues obtained after waste lithium ion batteries are recycled, then the structure of the graphite waste residues is repaired through amorphous carbon, and the graphite waste residues are recycled. And regenerating to prepare the graphite negative electrode material with excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of recycling waste lithium-ion batteries, and in particular to a method for deep purification and repairing and regenerating graphite residue from waste lithium-ion batteries. Background Art

[0002] Lithium-ion batteries are widely used as energy storage units in electric vehicles and large-scale power storage systems due to their high energy density, low self-discharge, and no memory effect. Therefore, the demand for lithium-ion batteries continues to expand and production continues to rise. However, due to the limited service life of lithium-ion batteries (usually between 3 and 10 years), a large amount of waste lithium-ion batteries is generated. In 2020 alone, the global production of waste lithium exceeded 150,000 tons, and is expected to reach 3.7 million tons by 2030.

[0003] Traditional recycling of waste lithium-ion batteries mainly focuses on the recovery of high-value metals in positive electrode materials, which have been successfully applied to industrial production through hydrometallurgy, pyrometallurgy and bioleaching technologies. In contrast, less attention has been paid to the recycling of negative electrode materials. Graphite negative electrode materials account for about 15% to 21% of the total mass in lithium-ion batteries and 10% to 15% of the total cost. Therefore, the development of waste graphite negative electrode recycling technology is very necessary from the perspective of economic and environmental benefits.

[0004] Graphite is a carbon-based material with excellent electrical and thermal conductivity. In the effective recovery and recycling of waste graphite, maintaining its high-quality crystallinity and layered structure is the key to obtaining recycled materials. The graphite slag obtained after acid leaching of current waste lithium battery materials still contains a large amount of metal ions and metallurgical residues, and the graphite particles in waste lithium-ion batteries may undergo chemical, surface and morphological degradation, which limits the direct reuse of graphite slag.

[0005] Therefore, there is an urgent need to provide a method for deep purification and repair and regeneration of waste lithium-ion battery graphite slag to solve the above problems. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings and defects of the prior art, provide a method for deep purification and repair and regeneration of waste lithium ion battery graphite slag, solve the problem of poor electrochemical performance of recycled graphite caused by metallurgical residues, poor particle uniformity and damaged structure in the graphite slag after hydrometallurgical treatment, and realize the deep purification and repair and regeneration of waste lithium ion battery graphite slag.

[0007] The objective of the present invention is achieved through the following technical solutions:

[0008] A method for deep purification and repair and regeneration of waste graphite residue from waste lithium-ion batteries, comprising the following steps: S1, uniformly mixing the graphite residue with ammonium persulfate powder to obtain a mixed powder;

[0009] S2, ball milling and pre-oxidation treatment of the mixed powder to obtain pre-oxidized graphite waste slag after ball milling treatment;

[0010] S3, the pre-oxidized graphite waste residue after ball milling is placed in deionized water for heating and stirring, and after heating, it is filtered and dried to obtain deeply purified graphite oxide;

[0011] S4, subjecting the deeply purified graphite oxide to asphalt cross-linking coating treatment;

[0012] S5. Carbonizing and sieving the coated product at high temperature to obtain a regenerated graphite negative electrode material.

[0013] As a preferred technical solution of the present invention, the ratio of graphite waste slag to ammonium persulfate powder in S1 is 10g:2-20g.

[0014] As a preferred technical solution of the present invention, the rotation speed of the ball mill in S2 is 200-600 rpm, and the ball milling time is 30-600 min.

[0015] As a preferred technical solution of the present invention, the ratio of the ball-milled graphite waste slag to deionized water in S3 is 30g:300-600ml, the heating temperature is 30-80°C, the stirring time is 30-90min, and the drying temperature is 60-100°C.

[0016] As a preferred technical solution of the present invention, the asphalt cross-linking coating treatment process in S4 includes:

[0017] L1. Dissolve asphalt in ethanol, add deeply purified graphite oxide, disperse by ultrasonic, and heat and stir in a water bath until dry;

[0018] L2. Cross-link and mix the asphalt and deeply purified graphite oxide in a water bath.

[0019] As a preferred technical solution of the present invention, the mass ratio of deeply purified graphite oxide, ethanol and asphalt in L1 is 1:3-10:0.05-0.2, the ultrasonic time is 5-10 minutes, and the water bath heating temperature is 60-80°C.

[0020] As a preferred technical solution of the present invention, the mass ratio of the deeply purified graphite oxide to asphalt in L2 is 1:0.05-0.2.

[0021] As a preferred technical solution of the present invention, the high temperature carbonization in S5 is specifically as follows: in an inert gas atmosphere, the temperature is increased to 400°C at a heating rate of 2-5°C / min, kept warm for 1 hour, and then the temperature is increased to 700-1000°C at a heating rate of 5°C / min, and kept warm for 2-4 hours.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention performs high-energy ball milling on graphite waste slag and ammonium persulfate, pre-oxidizes the graphite waste slag, shapes the particles, and converts the insoluble impurities into soluble sulfates, and then combines the water immersion process to achieve deep purification of the graphite waste slag, and then repairs the structure of the purified graphite slag by cross-linking asphalt with oxidized graphite and high-temperature coating, and regenerates and prepares graphite negative electrode materials with excellent electrochemical properties. The present application achieves uniform coating by cross-linking asphalt with oxidized purified graphite, and enhances the bonding between the amorphous carbon layer and graphite. High-temperature carbonization is then used to form amorphous carbon to repair the surface structure of the graphite waste slag, which reduces power consumption, so that the regenerated graphite negative electrode material has battery-grade performance and is easy to industrialize; and the regeneration and recovery of the graphite waste slag generated in the recycling process of waste lithium-ion batteries is achieved. The method is simple to operate, has high production efficiency, and has a low risk of environmental pollution, meeting the needs of industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a schematic diagram of the process of the present invention.

[0025] Figure 2 This is a test diagram of lithium storage blue electricity cycle of graphite before regeneration, regenerated graphite 1, regenerated graphite 2, and regenerated graphite 3 in specific embodiment 1 of the present invention.

[0026] Figure 3 This is a diagram of the first coulombic efficiency of lithium storage in the graphite before regeneration, regenerated graphite 1, regenerated graphite 2, and regenerated graphite 3 in specific embodiment 1 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0028] The present application aims to solve the problems of waste of negative electrode graphite caused by the prior art in recycling lithium-ion batteries, as well as poor electrochemical performance of recycled graphite caused by metallurgical residues, poor particle uniformity and damaged structure in graphite waste slag after hydrometallurgical treatment.

[0029] The specific implementation process of the present invention is as follows:

[0030] like Figure 1 As shown, a method for deep purification and repair and regeneration of waste lithium-ion battery graphite residue comprises the following steps:

[0031] S1, uniformly mixing graphite waste slag and ammonium persulfate powder to obtain a mixed powder;

[0032] S2, ball milling and pre-oxidation treatment of the mixed powder to obtain pre-oxidized graphite waste slag after ball milling treatment;

[0033] S3, the pre-oxidized graphite waste residue after ball milling is placed in deionized water for heating and stirring, and after heating, it is filtered and dried to obtain deeply purified graphite oxide;

[0034] S4, subjecting the deeply purified graphite oxide to asphalt cross-linking coating treatment;

[0035] S5. Carbonizing and sieving the coated product at high temperature to obtain a regenerated graphite negative electrode material.

[0036] Optionally, in this embodiment, the graphite waste residue is waste slag produced by hydrometallurgical recovery of the negative electrode of waste lithium-ion batteries. The graphite waste residue and ammonium persulfate powder are first uniformly mixed in a certain proportion to obtain a mixture, and the graphite waste residue is oxidized by the oxidation of ammonium persulfate; the mixture is then ball-milled, and the graphite waste residue particles are shaped and defects are introduced by the high-energy ball milling process. At the same time, the instantaneous high temperature generated by the ball milling is used to enhance the conversion of insoluble metal impurities into soluble sulfates by ammonium persulfate, and the oxygen generated by the decomposition of ammonium persulfate can also pre-oxidize the waste graphite to obtain the final ball-milled graphite waste residue. The ball-milled graphite waste residue is placed in a container filled with deionized water according to a certain solid-liquid ratio, and heated and stirred. The hydraulic impact helps to further dissociate the graphite waste residue particles and remove the soluble sulfate in the graphite waste residue; at the same time, thanks to the ball-milled waste graphite treatment, the strong oxidizing free radicals released by ammonium persulfate in water can further oxidize the defects of graphite. After the heating is completed, the graphite is separated from the waste water by filtering, and then dried in an oven to obtain deeply purified oxidized graphite. The difficulty of oxidizing waste graphite with ammonium persulfate is reduced by pretreatment with ball milling. In order to improve the performance of graphite, the deeply purified oxidized graphite is cross-linked and coated with asphalt according to the mass ratio; before this step, the asphalt is finely ground or sieved to make its particle size large enough to pass through a 200-mesh sieve, which helps to improve the performance of the asphalt, improve its dispersibility, and increase its mixing uniformity with graphite. By coating with asphalt powder, the negative electrode material of lithium-ion battery can be modified, the side reaction between the negative electrode material and the electrolyte can be reduced, the structural stability of the negative electrode material can be maintained, and the cycle life of the battery can be extended; at the same time, the co-embedding phenomenon of the electrolyte can be prevented, and the irreversible capacity of the graphite can be reduced; and the conductivity of the negative electrode material can be improved, and the resistance inside the electrode can be reduced, thereby improving the capacity and energy density of the battery. Finally, the coated product is subjected to high-temperature carbonization, and the volatile components in the asphalt are removed by high-temperature carbonization, so that it is converted into a more stable carbonaceous material, and the structural stability of the graphite is enhanced, and then the regenerated graphite negative electrode material that meets the particle size requirements is separated by screening. The regenerated graphite negative electrode material obtained by the above steps has excellent electrochemical properties. By ball milling graphite waste slag and ammonium persulfate, combined with water immersion process, deep purification of graphite waste slag is achieved. Abandoning the technical means of relying on high-concentration strong acid treatment in the traditional graphite waste slag impurity removal process, the efficient removal of metal ion impurities in graphite waste slag is achieved under the conditions of water washing and weak acid. At the same time, the waste graphite was oxidized by ball milling with ammonium persulfate. The asphalt and the purified oxidized graphite were cross-linked to achieve uniform coating and enhance the bonding between the amorphous carbon layer and the graphite. High-temperature carbonization was then used to form amorphous carbon to repair the surface structure of the waste graphite residue, which reduced power consumption and made the regenerated graphite negative electrode material have battery-grade performance, thus realizing the regeneration and recycling of the waste graphite residue generated in the recycling process of waste lithium-ion batteries.The deep purification and repair regeneration method is simple to operate, has high production efficiency, and meets the needs of industrial production.

[0037] The present invention will be further described below in conjunction with specific embodiments.

[0038] Example 1

[0039] The graphite waste slag and ammonium persulfate were mixed uniformly at a mass ratio of 2:1 to obtain a mixed powder; the mixed powder was ball-milled at a speed of 600r / min for 1h, and the graphite waste slag particles were shaped and the structure was restored by high-energy ball milling. At the same time, the instantaneous high temperature generated by the ball milling was used to enhance the ammonium persulfate to convert metal impurities into soluble sulfates to obtain the ball-milled graphite waste slag; the ball-milled graphite waste slag was put into superionized water at a solid-liquid ratio of 1g:20ml, stirred uniformly, and heated in a water bath at 80℃ for 90min, and the strong oxidizing property of ammonium persulfate was used to oxidize the graphite, and the graphite waste slag particles were further dissociated by hydraulic impact. The water-soluble sulfate in the graphite residue was removed, and the residue was filtered and dried in an oven at 80°C for 2 h to obtain deeply purified graphite oxide; the deeply purified graphite oxide was evenly mixed with asphalt powder after passing through 200 mesh in mass ratios of 10:0.5, 10:1, and 10:2, respectively, to obtain mixture 1, mixture 2, and mixture 3; mixture 1, mixture 2, and mixture 3 were placed in a high-temperature furnace, and argon was introduced to heat the mixture to 400°C at a heating rate of 5°C / min, and the mixture was kept warm for 1 h, and then the mixture was heated to 1000°C at a heating rate of 5°C / min, and the temperature was kept warm for 2 h, to obtain regenerated graphite 1, regenerated graphite 2, and regenerated graphite 3.

[0040] Under the same operation steps and parameters, different ratios of graphite and asphalt coating can obtain regenerated graphite with different properties. Chemical tests, such as Figures 2 to 3 shown.

[0041] Example 2

[0042] The graphite waste slag and ammonium persulfate were mixed uniformly at a mass ratio of 2:1 to obtain a mixed powder; the mixed powder was ball-milled at a speed of 600r / min for 30min, and the graphite waste slag particles were shaped and the structure was restored by high-energy ball milling. At the same time, the instantaneous high temperature generated by the ball milling was used to enhance the ammonium persulfate to convert metal impurities into soluble sulfates to obtain the ball-milled graphite waste slag; the ball-milled graphite waste slag was put into superionized water at a solid-liquid ratio of 1g:20ml, stirred uniformly, and heated in a water bath at 80℃ for 90min, and the strong oxidizing property of ammonium persulfate was used to oxidize the graphite waste slag. The graphite residue particles are further dissociated by hydraulic impact, and the water-soluble sulfate in the graphite residue is removed. After filtration, the graphite residue is dried in an oven at 80°C for 2 hours to obtain deeply purified graphite oxide; the deeply purified graphite oxide is evenly mixed with asphalt powder after passing through 200 meshes at a mass ratio of 10:1; the obtained mixture is put into a high-temperature furnace, and argon is introduced to heat the mixture to 400°C at a heating rate of 5°C / min, and the mixture is kept warm for 1 hour, and then the mixture is heated to 1000°C at a heating rate of 5°C / min, and the heating time is 2 hours to obtain regenerated graphite.

[0043] Example 3

[0044] The graphite waste slag and ammonium persulfate are mixed uniformly at a mass ratio of 1:1 to obtain a mixed powder; the mixed powder is ball-milled at a speed of 400r / min for 1h, and the graphite waste slag particles are shaped and the structure is restored by high-energy ball milling. At the same time, the instantaneous high temperature generated by the ball milling is used to enhance the ammonium persulfate to convert metal impurities into soluble sulfates to obtain the ball-milled graphite waste slag; the ball-milled graphite waste slag is put into superionized water at a solid-liquid ratio of 1g:20ml, stirred uniformly, and heated in a water bath at 80℃ for 90min, and the strong oxidizing property of ammonium persulfate is used to oxidize the graphite. The graphite waste particles are further dissociated by hydraulic impact, and the water-soluble sulfate in the graphite slag is removed. After filtration, the mixture is dried in an oven at 80°C for 2 hours to obtain deeply purified graphite oxide; the deeply purified graphite oxide is evenly mixed with asphalt powder after passing through 200 meshes in a mass ratio of 10:1; the obtained mixture is placed in a high-temperature furnace, and argon is introduced to heat the mixture to 400°C at a heating rate of 5°C / min, and the mixture is kept warm for 1 hour, and then the mixture is heated to 1000°C at a heating rate of 5°C / min, and the heating time is 2 hours to obtain regenerated graphite.

[0045] Example 4

[0046] The graphite waste slag and ammonium persulfate were mixed uniformly at a mass ratio of 2:1 to obtain a mixed powder; the mixed powder was ball-milled at a speed of 600r / min for 1h, and the graphite waste slag particles were shaped and the structure was restored by high-energy ball milling. At the same time, the instantaneous high temperature generated by the ball milling was used to enhance the ammonium persulfate to convert metal impurities into soluble sulfates to obtain the ball-milled graphite waste slag; the ball-milled graphite waste slag was put into superionized water at a solid-liquid ratio of 1g:20ml, stirred uniformly, and heated in a water bath at 80℃ for 90min, and the graphite was oxidized by the strong oxidizing property of ammonium persulfate, and the graphite waste slag particles were oxidized by hydraulic impact. The particles are further dissociated, and the water-soluble sulfate in the graphite slag is removed. After filtering, the slag is dried in an oven at 80°C for 2 hours to obtain deeply purified graphite oxide; the deeply purified graphite oxide is coated with ethanol and asphalt in a mass ratio of 1:5:0.1 in a beaker, and dispersed by ultrasound for 5 minutes, and then heated in an 80°C water bath with stirring until dry to obtain a dry product; the obtained product is placed in a high-temperature furnace, and argon is introduced to heat the product to 400°C at a heating rate of 5°C / min, and the temperature is kept for 1 hour, and then the temperature is increased to 1000°C at a heating rate of 5°C / min, and the temperature is kept for 2 hours to obtain regenerated graphite.

[0047] Example 5

[0048] The graphite waste slag and ammonium persulfate are mixed uniformly at a mass ratio of 2:1 to obtain a mixed powder; the mixed powder is ball-milled at a speed of 600r / min for 1h, and the graphite waste slag particles are shaped and the structure is restored by high-energy ball milling. At the same time, the instantaneous high temperature generated by the ball milling is used to enhance the ammonium persulfate to convert metal impurities into soluble sulfates to obtain the ball-milled graphite waste slag; the ball-milled graphite waste slag is put into superionized water at a solid-liquid ratio of 1g:20ml, stirred uniformly, and heated in a water bath at 80℃ for 90min, and the strong oxidizing property of ammonium persulfate is used to oxidize the graphite. The graphite waste particles are further dissociated by hydraulic impact, and the water-soluble sulfate in the graphite slag is removed. After filtration, the mixture is dried in an oven at 80°C for 2 hours to obtain deeply purified graphite oxide; the deeply purified graphite oxide is evenly mixed with asphalt powder after passing through 200 meshes in a mass ratio of 10:2; the obtained mixture is placed in a high-temperature furnace, and argon is introduced to heat the mixture to 400°C at a heating rate of 5°C / min, and the mixture is kept warm for 1 hour, and then the mixture is heated to 1000°C at a heating rate of 5°C / min, and the heating time is 2 hours to obtain regenerated graphite.

[0049] Example 6

[0050] The graphite waste slag and ammonium persulfate are mixed uniformly at a mass ratio of 2:1 to obtain a mixed powder; the mixed powder is ball-milled at a speed of 600r / min for 1h, and the graphite waste slag particles are shaped and the structure is restored by high-energy ball milling. At the same time, the instantaneous high temperature generated by the ball milling is used to enhance the ammonium persulfate to convert metal impurities into soluble sulfates to obtain the ball-milled graphite waste slag; the ball-milled graphite waste slag is put into superionized water at a solid-liquid ratio of 1g:20ml, stirred uniformly, and heated in a water bath at 80℃ for 90min, and the strong oxidizing property of ammonium persulfate is used to oxidize the graphite. The graphite waste particles are further dissociated by hydraulic impact, and the water-soluble sulfate in the graphite slag is removed. After filtration, the mixture is dried in an oven at 80°C for 2 hours to obtain deeply purified graphite oxide; the deeply purified graphite oxide is evenly mixed with asphalt powder after passing through 200 meshes in a mass ratio of 10:1; the obtained mixture is placed in a high-temperature furnace, and argon is introduced to heat the mixture to 400°C at a heating rate of 5°C / min, and the mixture is kept warm for 1 hour, and then the mixture is heated to 1000°C at a heating rate of 5°C / min, and the heating time is 2 hours to obtain regenerated graphite.

[0051] The above-mentioned embodiments only express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for deep purification and repair and regeneration of waste lithium-ion battery graphite residue, characterized in that: The following steps are involved: S1, uniformly mixing graphite waste slag and ammonium persulfate powder to obtain a mixed powder; S2, ball milling and pre-oxidation treatment of the mixed powder to obtain pre-oxidized graphite waste slag after ball milling treatment; S3, the pre-oxidized graphite waste residue after ball milling is placed in deionized water for heating and stirring, and after heating, it is filtered and dried to obtain deeply purified graphite oxide; S4, subjecting the deeply purified graphite oxide to asphalt cross-linking coating treatment; S5. Carbonizing and sieving the coated product at high temperature to obtain a regenerated graphite negative electrode material.

2. A method for deep purification and repair and regeneration of waste lithium-ion battery graphite residue according to claim 1, characterized in that: The ratio of graphite waste slag to ammonium persulfate powder in S1 is 10g:2-20g.

3. A method for deep purification and repair and regeneration of waste lithium-ion battery graphite residue according to claim 1, characterized in that: The rotation speed of the ball mill in S2 is 200-600 rpm, and the ball milling time is 30-600 min.

4. A method for deep purification and repair and regeneration of waste lithium-ion battery graphite residue according to claim 1, characterized in that: The ratio of the ball-milled graphite waste slag to deionized water in S3 is 30g:300-600ml, the heating temperature is 30-80°C, the stirring time is 30-90min, and the drying temperature is 60-100°C.

5. A method for deep purification and repair and regeneration of waste lithium-ion battery graphite residue according to claim 1, characterized in that: The asphalt cross-linking coating treatment process in S4 includes: L1. Dissolve asphalt in ethanol, add deeply purified graphite oxide, disperse by ultrasonic, and heat and stir in a water bath until dry; L2. Cross-link and mix the asphalt and deeply purified graphite oxide in a water bath.

6. A method for deep purification and repair and regeneration of waste lithium-ion battery graphite residue according to claim 5, characterized in that: The mass ratio of deeply purified graphite oxide, ethanol and asphalt in L1 is 1:3-10:0.05-0.2, the ultrasonic time is 5-10 minutes, and the water bath heating temperature is 60-80°C.

7. The method for deep purification and repair and regeneration of waste graphite residue from waste lithium-ion batteries according to claim 5, characterized in that: The mass ratio of the deeply purified graphite oxide to asphalt in the L2 is 1:0.05-0.

2.

8. The method for deep purification and repair and regeneration of waste lithium-ion battery graphite residue according to claim 5, characterized in that: The high temperature carbonization in S5 is specifically as follows: in an inert gas atmosphere, the temperature is increased to 400°C at a heating rate of 2-5°C / min, kept at that temperature for 1 hour, and then the temperature is increased to 700-1000°C at a heating rate of 5°C / min, and kept at that temperature for 2-4 hours.

Citation Information

Patent Citations

  • Graphite compound modification method and lithium ion battery anode material preparation method

    CN102544510A

  • High-performance lithium ion battery graphite negative electrode material and preparation method thereof

    CN111333064A

  • Recycling method of graphite negative electrode, negative electrode material and lithium ion battery

    CN117865146A

  • Method for repairing negative electrode graphite for waste lithium ion battery

    CN118712551A

  • Waste lithium battery graphite purification, repair and regeneration method, graphite negative pole piece and lithium battery

    CN119864534A